Effects of non-vascularized adipose tissue transplantation on its genetic profile. (1st January 2021) - Schreiter, Jeannine S.; Kurow, L. O; Langer, S; Steinert, M; Massier, L
ABSTRACT: Subcutaneous adipose tissue (SAT) is recognized as a highly active metabolic and inflammatory tissue. Interestingly, adipose tissue transplantation is widely performed in plastic surgery via lipofilling, yet little is known about the gene alteration of adipocytes after transplantation. We performed an RNA-expression analysis of fat transplants before and after fat transplantation. In C57BL/6 N mice SAT was autologously transplanted. Samples of SAT were analysed before transplantation, 7, and 15 days after transplantation and gene expression profiles were measured. Analysis revealed that lipid metabolism-related genes were downregulated while inflammatory and extracellular matrix related genes were up-regulated 7 and 15 days after transplantation. When comparing gene expression profile 7 days after transplantation to 15 days after transplantation developmental pathways showed most changes.